ANALISIS PENGGUNAAN BAHASA PROKEM DALAM MEDIA SOSIAL - Dina Syifa Istiqomah; Dini Syifa Istiqomah; Via Nugraha (IKIP Siliwangi, 2018)
Research in this journal relates to the definition of prokem language, language analysis of the prokem, as well as the use of language prokem in social media . Prokem language is a slang language in certain circles and has become a colloquial language that is used by the public. Social media play a role for the spread of language p rokem more broadly, because social media is one way people to communicate between individuals with individuals and groups in a group. In addition, social media also penye bab the existence of language variations . The use of language in this social media prokem, will be examined using qualitative descriptive method to process data. Data collected by using simak method assisted by advanced technique in the form of technique of note and technique used is random sampling technique. The data taken comes from social media such as facebook, whatsapp, line, and instagram. This study examines the canges based on phonological structure, the language vocabulary of the prokem, the process of formation of the morphological language of the prokem, and the type of meaning in the language of the prokem.